2022
DOI: 10.29040/ijebar.v6i1.4075
|View full text |Cite
|
Sign up to set email alerts
|

Affect of Job Satisfaction, Work Stress, and Work Environment on Potential Turnover Intention of Operator Level Employees at Pt. Prima Sejati Sejahtera 3

Abstract: The purpose of this study is to determine job satisfaction, work stress, and work environment on turnover intention at PT. Prima Sejati Sejahtera 3 to the operator level employees. High employee turnover rates result in organizations are becoming ineffective, losing experienced employees and needing to train new employees. High job satisfaction and a good work environment will affect the decrease in turnover intention, while high work stress will affect the increase in turnover intention. The variables u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
0
0
0
2
Order By: Relevance
“…The findings from this research also confirm or support the results of previous research by Meilano and Nugraheni (2017), Pramudika et al (2017), Putra and Utama (2017), Anggareini and Suryalena (2019), Venisa and Brahmana (2020) and Ernawati et al (2022) who also found a negative influence of the work environment on turnover intention. Meilano and Nugraheni (2017) explained that a work environment that is not conducive or comfortable for a worker will make them feel uncomfortable working in a company which will then encourage them to look for work in another company that offers or is seen as having a better working environment.…”
Section: Discussion the Relationship Between Work Environment And Tur...supporting
confidence: 91%
See 2 more Smart Citations
“…The findings from this research also confirm or support the results of previous research by Meilano and Nugraheni (2017), Pramudika et al (2017), Putra and Utama (2017), Anggareini and Suryalena (2019), Venisa and Brahmana (2020) and Ernawati et al (2022) who also found a negative influence of the work environment on turnover intention. Meilano and Nugraheni (2017) explained that a work environment that is not conducive or comfortable for a worker will make them feel uncomfortable working in a company which will then encourage them to look for work in another company that offers or is seen as having a better working environment.…”
Section: Discussion the Relationship Between Work Environment And Tur...supporting
confidence: 91%
“…Research conducted by experts such as Meilano and Nugraheni (2017); Pramudika et al (2017); Men and Main (2017); Anggareini and Suryalena (2019); Venisa and Brahmana (2020); and Ernawati et al (2022) explains that the work environment has a negative influence on turnover intention, meaning that the higher or better the work environment conditions perceived by the workforce, the lower the level of turnover intention of the workforce, conversely if the work environment conditions perceived by the workforce are If it is bad, the turnover intention level of the workforce will increase. Therefore, it can be explained that the research hypothesis is:…”
Section: Literature Review the Relationship Between Work Environment ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Nilai pengujian job satisfaction terhadap turnover intention bernilai 0,015 yang berarti hipotesis kelima diterima sehingga terdapat pengaruh terhadap turnover intention. Hal ini juga mendukung penelitian yang dilakukan oleh Ernawati et al (2022) yang menyatakan job satisfaction berpengaruh secara negatif terhadap turnover intention. Sehingga dapat disimpulkan bahwa industri perbankan sudah memberikan kepuasan kerja yang baik pada karyawannya dengan meningkatkan lingkungan kerja karyawannya.…”
Section: Pembahasanunclassified
“…Namun pada hipotesis ketujuh yakni pengaruh secara tidak langsung yang dihasilkan work environment terhadap turnover intention akibat variabel mediasi job satisfaction memiliki nilai 0,084 yang berarti hipotesis ketujuh ditolak sehingga tidak terdapat pengaruh indirect effect terhadap turnover intention. Hal ini tidak sesuai dengan penelitian yang dilakukan oleh Ernawati et al (2022) yang menyatakan bahwa work environment dimediasi oleh job satisfaction terhadap turnover intention. Hal ini disebabkan karena karyawan pada industri perbankan tidak terganggu dengan tidak adanya work environment yang baik pada lingkungan mereka bekerja sehingga menyebabkan tidak terpengaruhinya turnover intention.…”
Section: Pembahasanunclassified